Percepção dos profissionais de enfermagem frente a processos de morte: influência da espiritualidade - DORNFELD, Raquel Lima (2017)
Social representations attributed to finitude reveals a cultural-historical context which directly influences individual perceptions and attitudes.The nursing team, when taking care for patients in the death process, may encounter situations that cause psychic and emotional weakening. Spirituality is a dimension that can help professionals deal more salutarily with aspects related to finitude, provide humanized actions that consolidate the integrality of care, and also obtain benefits for their own health. Through a qualitative design, the study sought to understand the influence of spirituality in relation to the death process in nursing practice. Were interviewed 160 professionals, among them nurses and assistants, who works in the emergency and hospitalization settings from a medium and high complexity hospital. The analysis of collected testimonies was made through Discourse of Collective Subject technique, using the software DSCsoft. It is observed that professionals value and seek to develop aspects related to spirituality, both in relation to transcendence and in their relationship with others and the environment where they lives. However, it is observed the difficulty to looking back at themselves. It's suggested, through continuing education strategies, the improvement of aspects related to good practices, with the goal to the best assistance in such circumstances. However, the creation of listening and welcoming spaces to the experiences lived and shared by these professionals can subsidize opportunities for individual and collective growth, in regard to the re-signification of care in the face of death processes.